Road safety in India: A Public Health Concern - Parsekar, Shradha S; Singh, Mannat M; Venkatesh, Bhumika T; Nair, Sreekumaran N (Indian Journal of Community Health, 2015)
Introduction: Road traffic accident (RTA) is one of the major preventable public health problems and is on the rise which can be attributed to increase in the number of vehicles and lifestyle changes and risky attitudes. This paper is intended to search for available published information which in turn might help the policy makers as well as practitioners to make use of it. Methods: The information has been gathered from papers related to RTAs from various databases such as PubMed, Google scholar, government websites to get an overview in India for the last 15 years. Result and Conclusion: The burden of RTA was found to be considerably high globally as well as in India. RTA causes a number of effects which can be: economical, physical, psychological and social. The burden of RTA is on the rise which makes it necessary to take a multi-sectoral approach in its prevention and control